2019
DOI: 10.1364/josaa.36.000809
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the dynamics of time-varying phase aberrations from time histories of the point-spread function

Abstract: To optimally compensate for time-varying phase aberrations with adaptive optics, a model of the dynamics of the aberrations is required to predict the phase aberration at the next time step. We model the time-varying behavior of a phase aberration, expressed in Zernike modes, by assuming that the temporal dynamics of the Zernike coefficients can be described by a vector-valued autoregressive (VAR) model. We propose an iterative method based on a convex heuristic for a rank-constrained optimization problem, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…However, because the problem is non-convex, such a method is typically prone to local minimas. In our experiments it has been shown that convergence to a good solution is difficult unless the initial guess is very close to the optimal solution [7]. Therefore, it is paramount to find an alternative strategy to solve this problem.…”
Section: Bilinear Matrix Equalitiesmentioning
confidence: 91%
See 1 more Smart Citation
“…However, because the problem is non-convex, such a method is typically prone to local minimas. In our experiments it has been shown that convergence to a good solution is difficult unless the initial guess is very close to the optimal solution [7]. Therefore, it is paramount to find an alternative strategy to solve this problem.…”
Section: Bilinear Matrix Equalitiesmentioning
confidence: 91%
“…Finally, consider the RMP that spawned from replacing a bilinearity with a linear rank constraint in Equation (2.41): where λ ∈ R + is a regularization parameter [7].…”
Section: Implementation Of Heuristicmentioning
confidence: 99%
“…Fourier optics approximation) always cause mismatches between the real system and the state-space model. Recently, data-driven approaches have been developed to achieve system identification using a telescope's point spread function (PSF) images [39] or real-time wavefront control data [40,41]. One of the experimentally verified approaches [40] uses an E-M algorithm to identify model parameters, which iteratively reconstructs the hidden electric field (E-step) and updates system's Jacobian matrix (M-step).…”
Section: Methods: Broadband Control and Reduced-dimensional System Idmentioning
confidence: 99%
“…Moreover, by including the temporal and statistical models of the turbulence and sensors, KF is known to be robust against modeling errors and measurement noise, making it particularly suitable for dealing with dynamic aberrations and noisy measurements. Small-phase aberrations have also been assumed in other algorithms that aim to estimate temporal dynamic aberrations [15,16]. Possible applications include estimating NCPAs (which occur in various fields such as astronomy [17,18] and ophthalmology [19,20]), wind induced dynamic non-common path vibrations [21], or the low-wind effect [18].…”
Section: Research Articlementioning
confidence: 99%